PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MEDIA SOSIAL TERHADAP NIAT BERWIRAUSAHA MELALUI POLA PIKIR KEWIRAUSAHAAN SEBAGAI VARIABEL MEDIASI PADA MAHASISWA FKIP UNS - Dina Ayu Fauza; Silky Roudhotus Sa’adah (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Entrepreneurial intention plays a crucial role in encouraging university students to pursue a career as entrepreneurs. This study aims to examine the influence of entrepreneurship education and social media on entrepreneurial intention, with entrepreneurial mindset serving as a mediating variable among students of the Faculty of Teacher Training and Education (FKIP) at UNS. A quantitative approach utilizing a survey method was employed. The study population consisted of active students from the Economic Education, Office Administration Education, and Accounting Education study programs (classes of 2022–2023) who had completed an entrepreneurship course. A probability sampling technique specifically proportionate stratified random sampling was used to select a sample of 131 students. Data were collected via Likert-scale questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with SmartPLS software. The results indicate that entrepreneurship education, social media, and entrepreneurial mindset all exert a positive and significant influence on entrepreneurial intention. Furthermore, entrepreneurial mindset mediates the relationship between entrepreneurship education/social media and entrepreneurial intention. These findings highlight the importance of strengthening students' entrepreneurial mindset as a connecting factor, thereby enabling entrepreneurship education and social media to more effectively foster entrepreneurial intention. Keywords: entrepreneurship education, social media, entrepreneurial intentions, entrepreneurial mindset